Student Folk Crafts In Teaching Art Strategy Of Using The "Cluster" Method - Шомирзаев Махматмурод Хурамович (Genius Journals, 2024)
This article explains the use of the cluster method in folk crafts as an example of embroidery
Keywords: decoration; crafts; craftsmanship; education